2000
DOI: 10.1046/j.1365-2273.2000.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of high resolution computed tomography in the assessment of cochlear implant patients

Abstract: High resolution computed tomography (HRCT) of the temporal bone is performed routinely in the preoperative evaluation for cochlear implantation. The largest multicentre retrospective analysis of data was undertaken to compare the findings on HRCT with the surgical findings in an attempt to determine the accuracy of HRCT. Of the 1009 patients referred, 525 were scanned of whom 335 were implanted. As part of this study we were also able to identify both radiological and non-radiological reasons for rejection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…Meningitis is one of the most common causes of acquired hearing loss in children and adults (Nadol, 1978;Nair et al, 2000). In our study meningitis was most commonly caused by Neisseria meningitidis and least commonly by Haemophilus infl uenzae.…”
Section: Discussionmentioning
confidence: 93%
“…Meningitis is one of the most common causes of acquired hearing loss in children and adults (Nadol, 1978;Nair et al, 2000). In our study meningitis was most commonly caused by Neisseria meningitidis and least commonly by Haemophilus infl uenzae.…”
Section: Discussionmentioning
confidence: 93%
“…In the study of Nikolopoulos et al (17), CT images showed a sensitivity of 62% and a specificity of 82% for the detection of cochlear ossification in a group of 44 children. HRCT findings in patients deafened by meningitis assessed by Nair et al (18) were reported to possess a sensitivity of 71% and a specificity of 100%.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported that the sensitivity of high resolution CT imaging in detect otosclerosis is between 71–78% (16,17). In a case series of nine patients, ossification of the round window was evident on imaging in 4/9 patients.…”
Section: Discussionmentioning
confidence: 99%